Direitos humanos e dependência no período Pós-Independência em Moçambique - Magule, Adérito Arlindo (Argumentum, 2025)
This study analyses the determining correlations of Human Rights in the context of peripheral countries, with a particular focus on Mozambique’s dependency on core economies in the post-independence period (1975–present). It aims to describe the dialectic of human rights development in peripheral countries based on World-Systems Theory and to analytically delineate the “human rights issue” in Mozambique in the post-independence period. Methodologically, this is a qualitative study with a descriptive objective, carried out through bibliographic and documentary reviews. The study found that although Mozambique has legislation addressing human rights issues, civil war, poverty, and economic dependency have eroded human rights. There has been a resurgence of hun@ger hotspots, precarious primary healthcare and education, and a lack of freedom of expression and assembly.